2018
DOI: 10.1007/s00296-018-4180-4
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes with golimumab in patients with rheumatoid arthritis, psoriatic arthritis, and ankylosing spondylitis: non-interventional study GO-NICE in Germany

Abstract: The TNF inhibitor golimumab (GLM) is a treatment option in patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA), and ankylosing spondylitis (AS). The GO-NICE study assessed patient-reported outcomes (PRO) in patients newly treated with monthly GLM 50 mg subcutaneously (SC) under real-life conditions in Germany. A prospective non-interventional study with 24-month observation per patient was conducted at 158 sites. Available for analysis were 1,458 patients, 474 with rheumatoid arthritis (RA: 54.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
35
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 41 publications
9
35
0
5
Order By: Relevance
“…Due to its long-term duration, BioTRAC offered a unique opportunity to evaluate the real-world effectiveness and safety of three anti-TNF agents in a community Canadian setting, while assessing regional variations due to differences in patient profiles, practice patterns and local reimbursement policies impacting access to care over 16 years. Although there has been extensive real-world evidence generated on the early anti-TNF agents such as IFX or etanercept, very little efficacy data has been published with other anti-TNF agents such as GLM, and most of those only presented persistence data (15,(29)(30)(31). One exception, however, is the GO NICE prospective non-interventional trial in Germany for inflammatory arthritis patients treated with GLM (15,32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its long-term duration, BioTRAC offered a unique opportunity to evaluate the real-world effectiveness and safety of three anti-TNF agents in a community Canadian setting, while assessing regional variations due to differences in patient profiles, practice patterns and local reimbursement policies impacting access to care over 16 years. Although there has been extensive real-world evidence generated on the early anti-TNF agents such as IFX or etanercept, very little efficacy data has been published with other anti-TNF agents such as GLM, and most of those only presented persistence data (15,(29)(30)(31). One exception, however, is the GO NICE prospective non-interventional trial in Germany for inflammatory arthritis patients treated with GLM (15,32).…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been extensive real-world evidence generated on the early anti-TNF agents such as IFX or etanercept, very little efficacy data has been published with other anti-TNF agents such as GLM, and most of those only presented persistence data (15,(29)(30)(31). One exception, however, is the GO NICE prospective non-interventional trial in Germany for inflammatory arthritis patients treated with GLM (15,32). This 2-year trial also found significant clinical effectiveness among RA patients (15), as well as improvements in patient-reported health status, physical function, and fatigue levels (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Таблица 3. Динамика оцениваемых параметров в исследовании GO-NICE[21] Table 3. Dynamics of the assessed parameters in the GO-NICE study[21] Примечание.…”
unclassified
“…Динамика оцениваемых параметров в исследовании GO-NICE[21] Table 3. Dynamics of the assessed parameters in the GO-NICE study[21] Примечание. DAS28 -индекс активности ревматоидного артрита по 28 суставам, ОСБ -общее состояние больных, PsARC -индекс Американского колледжа ревматологов для псориатического артрита, BASDAI -индекс активности анкилозирующего спондилита.…”
unclassified